Public Access, Open Access, and the Need for NIH Governance - Adam A. Markovitz; Himali M. Weerahandi; Audrey D. Zhang; Timothy S. Anderson (JAMA Internal Medicine, 2026)
This Viewpoint discusses the confusion between public access and open access, pay-to-comply publisher practices, and the steps that the National Institutes of Health (NIH) must take to fill this gap and promote public access goals.